Students’ Mathematical Reasoning Errors in Solving Computer Based Written Exam Model Questions Based on Newman’s Theory - Disnawati, Hermina; Deda, Yohanis Ndapa; Salsinha, Cecilia Novianti; Bees, Nene Lodiana (Universitas Jambi, Indonesia, 2023)
Mathematical reasoning is an essential ability that must be possessed by students when studying at university or in real life. Mathematical reasoning ability is one of the material sub-topics tested in the 2019 computer based written exam. In solving mathematical reasoning content questions, students often make mistakes in answering questions. The mistakes made by students occur due to various factors. Therefore, this research aimed to describe student errors and the factors that caused student errors in solving computer based written exam questions on the topic of mathematical reasoning according to Newman's theory. This research used a mixed method with 28 class XII students as the research subjects. The research instruments were written tests and interviews. The factors that caused reading errors were because students could not interpret the questions properly, misunderstandings occurred because students could not determine the necessary information in the problem, transformation errors occurred because students could not determine the correct method to solve the problem, process skill errors occurred because students were less thorough in solving questions and because of previous mistakes, mistakes in writing the final answer occurred because students were not used to writing conclusions and also because they were in a hurry.